2017
DOI: 10.1016/j.jadohealth.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Psychosocial Outcomes of a Structured Transition Program Among Young Adults With Type 1 Diabetes

Abstract: Purpose We identified and treated young adults with type 1 diabetes who had been lost to follow-up during their transfer from pediatric to adult care, comparing their clinical, psychosocial, and healthcare utilization outcomes to participants receiving continuous care throughout the transition to adult care. Methods Individuals in their last year of pediatric care (“Continuous Care” group, CC, n=51) and individuals lost to follow-up in the transfer to adult care (“Lapsed Care” Group, LC, n=24) were followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(69 citation statements)
references
References 21 publications
0
69
0
Order By: Relevance
“…Differences in blood glucose control were measured in 15 studies. Of these, four studies found no differences, while 11 studies found improvements in glycaemic control . Improvements in physical activity or greater adherence to behavioural support were reported in all studies that had measured physical activity .…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Differences in blood glucose control were measured in 15 studies. Of these, four studies found no differences, while 11 studies found improvements in glycaemic control . Improvements in physical activity or greater adherence to behavioural support were reported in all studies that had measured physical activity .…”
Section: Resultsmentioning
confidence: 94%
“…Management or frequency of symptoms was examined in 44 studies. Four of the studies that had investigated symptom frequency found no differences, and 25 studies reported reduction of symptoms and/or awareness of symptom triggers . Ten studies from interventions tailored to children and adolescents with asthma reported improved asthma control and decreased number of asthma exacerbations.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Current evidence suggests that well‐planned, effective transitional care can prevent deterioration in AYAs’ health and disengagement with health care; stable or improved disease control; improved knowledge, self‐management skills and patient satisfaction; improved relationships with healthcare professionals (HCPs) and parent satisfaction (Gabriel, McManus, Rogers, & White, ; Ladouceur et al, ; Mackie et al, ; Pyatak et al, ; van Staa, Sattoe, & Strating, ). In contrast, inadequate transition is associated with poor clinic attendance, loss to follow‐up; increased nonadherence to treatment, increased morbidities, lower physical well‐being, increased emergency/hospital admissions and adverse health outcomes (Garvey et al, ; Heery, Sheehan, While, & Coyne, ; Sheehan, While, & Coyne, ).…”
Section: Introductionmentioning
confidence: 99%